A REVIEW OF WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY - Nor Maslia binti Rasli Samudin; Nur Syaza Syamirah binti Azman; Mimi NurBalqis binti Noor Azmi; Rose Bathrisyia binti Mohd Rizal; Irdina Umairah binti Faizal (International Journal of Accounting, Finance and Business, 2022)
The most important factor affecting employee productivity is the workplace environment. Employee productivity, performance, health and safety, comfort, concentration, job satisfaction, and morale are all affected by the physical characteristics of the workplace environment. Workplace motivation is necessary, but the most important factor is internal motivation, which stimulates employees' desire to work hard and enthusiastically in order to increase production. When a person can carry out their activity optimally, healthily, safely, and comfortably, the environment is considered to be appropriate. Long-term, an incompatible environment evolves. Furthermore, adverse environmental conditions necessitate more energy and time, which is incompatible with efficient framework systems. This paper aims at presenting the reviews of the literature on workplace environment and employee productivity. In this research paper the existing literature on the workplace environment in organizations is being reviewed. The review will give a holistic understanding of the workplace environment and employee productivity concept for future researchers and aid to identify the research gap.